Omega-3 fatty acid composition of chicken plasma fed diets varying in LA to ALA ratio. Issue 1 (November 2021) - Kartikasari, L R; Hughes, R J; Geier, M S; Gibson, R A
Abstract: The impact of dietary supplementation of a vegetable source of n-3 fat in the form of alpha-linolenic acid (ALA, 18:3n-3) on the accumulation of n-3 fatty acids in plasma chicken was investigated. Sixty unsexed one-day-old broiler chickens were randomly allocated to six diets (n=10 birds/diet) for 4 weeks. The birds were fed a proprietary starter commercial feed for the first two days after hatch. Six dietary treatments ranging in fat content from 5 to 10% were prepared by supplementing the basal diet with vegetable oils. The ALA levels varied from 1 to 8% energy (%en). The n-6 fatty acid linoleic acid (LA, 18:2n-6) level was limited to less than 5%en. Results showed that the metabolites of dietary ALA, EPA, DPA, and DHA in plasma tissues increased in a curvilinear manner as dietary ALA increased, achieving 3- to 13-fold compared to the levels in the control birds (P<0.001). The total PUFA content of plasma samples increased (P<0.001) due to increasing the diets' ALA content, achieving 41.20% of the total fatty acids when the LA to ALA ratio of diets was at the lowest level. The increase in total PUFA was mainly due to an increase in total n-3 PUFA.